Stonehenge's Avenue and 'Bluestonehenge'. (19th July 2016) - Allen, Michael J.; Chan, Ben; Cleal, Ros; French, Charles; Marshall, Peter; Pollard, Joshua; Pullen, Rebecca; Richards, Colin; Ruggles, Clive; Robinson, David; Rylatt, Jim; Thomas, Julian; et al.
Abstract: Abstract : Stonehenge is a site that continues to yield surprises. Excavation in 2009 added a new and unexpected feature: a smaller, dismantled stone circle on the banks of the River Avon, connected to Stonehenge itself by the Avenue. This new structure has been labelled 'Bluestonehenge' from the evidence that it once held a circle of bluestones that were later removed to Stonehenge. Investigation of the Avenue closer to Stonehenge revealed deep periglacial fissures within it. Their alignment on Stonehenge's solstitial axis (midwinter sunset–midsummer sunrise) raises questions about the early origins of this ritual landscape.